2013
DOI: 10.1136/bcr-2012-008438
|View full text |Cite
|
Sign up to set email alerts
|

Solving the puzzle of strong French coffee, palpitation and dizziness

Abstract: SUMMARYA 38-year-old gentleman presented to the emergency department at the University Hospital in Geneva with nausea, rapid palpitation and presyncope. This was followed by a poor night's sleep, a day of strenuous walking in the city and drinking a large quantity of strong French coffee. 12-lead ECG revealed tachycardia with slightly increased QRS duration of right bundle branch block pattern and left axis deviation. Without the electrophysiological (EP) study, the patient was diagnosed with supraventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…3 En 1981, Belhassen et al, demostraron que el verapamilo era útil en su tratamiento y en la prevención de recurrencias. 4 Son típicas de varones jóvenes (15-40 años) y aunque suelen ocurrir en reposo, pueden inducirse por las catecolaminas en situaciones de estrés emocional o ejercicio. 5 Como el resto de las TV idiopáticas, se originan en pacientes sin evidencia de cardiopatía estructural, alteraciones electrolíticas, metabólicas o enfermedades eléctricas primarias.…”
Section: Taquicardias Ventricularesunclassified
“…3 En 1981, Belhassen et al, demostraron que el verapamilo era útil en su tratamiento y en la prevención de recurrencias. 4 Son típicas de varones jóvenes (15-40 años) y aunque suelen ocurrir en reposo, pueden inducirse por las catecolaminas en situaciones de estrés emocional o ejercicio. 5 Como el resto de las TV idiopáticas, se originan en pacientes sin evidencia de cardiopatía estructural, alteraciones electrolíticas, metabólicas o enfermedades eléctricas primarias.…”
Section: Taquicardias Ventricularesunclassified
“…Park and Grubb reported on a 38 year-old male patient with nausea, rapid palpitations, and presyncope, which occurred in association with the consumption of a large amount of strong French coffee. [14] His electrocardiogram showed a tachycardia with a slightly increased QRS duration of right bundle branch block pattern with left axis deviation and supraventricular tachycardia was initially diagnosed. With a subsequent electrophysiologic study, he was found to have a fascicular tachycardia as a rare presentation of ventricular tachycardia.…”
Section: Arrhythmiasmentioning
confidence: 99%